CASE STUDY. IMPACT OF SOCIAL MEDIA ON MENTAL HEALTH OF STUDENTS - Dilnoza Kamoliddinova; Fozilbek Orzibekov (TADQIQOTLAR, 2025)
Abstract Considering the significant and constant use of social networks in the world, mostly by young women, we reflect in this article on the relationship between digital communication technologies and their influence on student perspectives, as well as their  repercussions  on  mental  health  and  academic  performance.  The  aim  was  to describe the reasons that lead university students to access social networks; outline the harms  of  using  these  platforms,  if  any,  in  their  life  experiences;  investigate  the influence of social networks on their productivity, thus seeking to understand the use of social networks and their interface with the mental health of these students. This is a  descriptive-exploratory  study,  with  a  qualitative  approach,  carried  out  with  16 students of Kimyo International University in Tashkent (Samarkand Branch). A semi-structured  interview  was  used,  and  thematic  content  analysis  was  followed  for  its interpretation.  Information  collection  took  place  in  November  2019  and  all  ethical aspects were respected. The results indicated different perceptions regarding the use of social networks that produce impacts on the mental health, personal and academic lives of the university students interviewed. Furthermore, it was found that social networks contribute to the dynamism and autonomy of the learning process, while the excessive use of these platforms can have a detrimental effect on students' mental health and academic performance.